2017
DOI: 10.1002/mrd.22788
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic movement profiles of mouse surrounding nucleolus and not-surrounding nucleolus antral oocytes during meiotic resumption

Abstract: Full-grown mouse antral oocytes are classified as surrounding nucleolus (SN) or not-surrounding nucleolus (NSN), depending on the respective presence or absence of a ring of Hoechst-positive chromatin surrounding the nucleolus. In culture, both types of oocytes resume meiosis and reach the metaphase II (MII) stage, but following insemination, NSN oocytes arrest at the two-cell stage whereas SN oocytes may develop to term. By coupling time-lapse bright-field microscopy with image analysis based on particle imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Once again, this highlights the importance and predictive power of fertilisation events, as reported in recently published studies (Coticchio et al, 2018). Alternatively, the present approach could be extended to the cytoplasmic activity of human unfertilized oocytes, mirroring our previous mouse study (Bui et al, 2017).…”
Section: Discussionmentioning
confidence: 69%
“…Once again, this highlights the importance and predictive power of fertilisation events, as reported in recently published studies (Coticchio et al, 2018). Alternatively, the present approach could be extended to the cytoplasmic activity of human unfertilized oocytes, mirroring our previous mouse study (Bui et al, 2017).…”
Section: Discussionmentioning
confidence: 69%
“…To compare our approach to manual analysis, we presented the same 131 oocyte images to three reproductive biologists during their training period. These biologists had different levels of training experience (i.e., beginner, medium, and good) and their classification accuracy, compared to that of the expert, ranged from 78.7 to 84.5% 19 , quite lower than the accuracy of the automated approach.
Fig. 3Supervised data analysis of 131 mouse oocyte images with surrounded (SN) or not surrounded (NSN) chromatin organization.
…”
Section: Resultsmentioning
confidence: 99%
“…Two main different types of chromatin organization are present in antral mouse oocytes: Surrounded Nucleolus (SN) oocytes, with a ring of Hoechst-positive chromatin that surrounds the nucleolus, and non-surrounded nucleolus (NSN) oocytes, which lack the ring and exhibit a more dispersed chromatin . A recent study reported that 17.4% of NSN oocytes were arrested at the GV-stage compared with SN oocytes, which resumed meiosis completely [33].…”
Section: Introductionmentioning
confidence: 99%